Integration of aerobic granular sludge and membrane bioreactors for wastewater treatment. (18th August 2018) - Liébana, Raquel; Modin, Oskar; Persson, Frank; Wilén, Britt-Marie
Abstract: Environmental deterioration together with the need for water reuse and the increasingly restrictive legislation of water quality standards have led to a demand for compact, efficient and less energy consuming technologies for wastewater treatment. Aerobic granular sludge and membrane bioreactors (MBRs) are two technologies with several advantages, such as small footprint, high-microbial density and activity, ability to operate at high organic- and nitrogen-loading rates, and tolerance to toxicity. However, they also have some disadvantages. The aerobic granular sludge process generally requires post-treatment in order to fulfill effluent standards and MBRs suffer from fouling of the membranes. Integrating the two technologies could be a way of combining the advantages and addressing the main problems associated with both processes. The use of membranes to separate the aerobic granules from the treated water would ensure high-quality effluents suitable for reuse. Moreover, the use of granular sludge in MBRs has been shown to reduce fouling. Several recent studies have shown that the aerobic granular membrane bioreactor (AGMBR) is a promising hybrid process with many attractive features. However, major challenges that have to be addressed include how to achieve granulation and maintain granular stability during continuous operation of reactors. This paper aims to review the current state of research on AGMBR technology while drawing attention to relevant findings and highlight current limitations.